2012
DOI: 10.1371/journal.pone.0034820
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence from Studies of Soluble Protein Fragments that Knops Blood Group Polymorphisms in Complement Receptor-Type 1 Are Driven by Malaria

Abstract: Complement receptor-type 1 (CR1, CD35) is the immune-adherence receptor, a complement regulator, and an erythroid receptor for Plasmodium falciparum during merozoite invasion and subsequent rosette formation involving parasitized and non-infected erythrocytes. The non-uniform geographical distribution of Knops blood group CR1 alleles Sl1/2 and McCa/b may result from selective pressures exerted by differential exposure to infectious hazards. Here, four variant short recombinant versions of CR1 were produced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…CR1 interacts with two P. falciparum proteins, the malarial adhesin PfEMP1 (14) and the PfRh4 invasion ligand (15), but the binding sites have been located to the C3b and C4b binding sites of CR1, respectively (20,21). Consistent with these locations, Tetteh-Quarcoo et al (56) observed no difference between the Knops blood group variants McC a/b and Sl1/2 in the ability of the CR1 fragment CCP15-25 to interact with PfRh4 or to disrupt PfEMP1-dependent P. falciparum rosetting (56). It should be mentioned that the same study assigned the C1q binding site to a CR1 region encompassing CCPs 15-25, with a suggested major contribution of CCPs 15-17, using recombinant CR1 fragments produced in yeasts and treated with endoglycosidase H (56).…”
Section: Discussionmentioning
confidence: 81%
“…CR1 interacts with two P. falciparum proteins, the malarial adhesin PfEMP1 (14) and the PfRh4 invasion ligand (15), but the binding sites have been located to the C3b and C4b binding sites of CR1, respectively (20,21). Consistent with these locations, Tetteh-Quarcoo et al (56) observed no difference between the Knops blood group variants McC a/b and Sl1/2 in the ability of the CR1 fragment CCP15-25 to interact with PfRh4 or to disrupt PfEMP1-dependent P. falciparum rosetting (56). It should be mentioned that the same study assigned the C1q binding site to a CR1 region encompassing CCPs 15-25, with a suggested major contribution of CCPs 15-17, using recombinant CR1 fragments produced in yeasts and treated with endoglycosidase H (56).…”
Section: Discussionmentioning
confidence: 81%
“…Our study is also showing high expression of CR1 on RBCs facilitate binding of plasmodium and increased level of TNF-α Cytokine in blood. TNF-α is anti-inflammatory cytokine and act as a marker to malarial infection [24]. TNF-α level in Healthy and case population reveal strong association (P<0.0001***) that is similar to P.B.…”
Section: Discussionmentioning
confidence: 84%
“…The two copies of Site 2 (i.e. CCPs 8-10 and 15-17) bind C3b and C4b efficiently (Tetteh-Quarcoo et al, 2012) and act as cofactors for Factor I cleavage of C3b and C4b (Ross et al, 1982). In the full length ectodomain (which corresponds to soluble CR1 (sCR1)) these sites cooperate to bind the principle ligands C3b and C4b thus leading to higher affinities than observed for each single site (TettehQuarcoo et al, 2012;Tham et al, 2011).…”
Section: Complement Receptor 1 and Malariamentioning
confidence: 99%
“…Laboratory experiments with the E1590/G1601 phenotype showed reduction of rosette formation (Rowe et al, 1997). More recently the underlying Knops antigens were examined for their ability to influence CR1 functional activities, but no difference was found (Tetteh-Quarcoo et al, 2012). In addition, the Knops antigen variants did not exhibit any inhibition of either parasites invasion or rosette formation (Tetteh-Quarcoo et al, 2012).…”
Section: Cr1 Knops Blood Group Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation